THE INFLUENCE OF JAPANESE SOCIETY`S NEGATIVE STIGMA TO SHOKO TENDO`S PSYCHOLOGICAL CONDITION IN “YAKUZA MOON” - WIDYATMIKO, KURNIAWAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Japanese Society, Negative Stigma, Shoko Tendo, Yakuza, YakuzaMoon Society as the biggest term of family has a role to influence someone`s perspective toward a group and someone. Society`s influence can be positive or negative, depends on the track record by an individual or a group of people. Social phenomena is the one factor that influence the literary works. This also reflected in a memoir of Shoko Tendo, Yakuza Moon. Yakuza Moon is the Shoko Tendo`s first literary work which is portrayed all of Shoko Tendo`s experiences in her social life.Social psychological and biographical approaches are applied in this study because Yakuza Moon depicts how Shoko Tendo`s psychological condition is influenced by her schoolmates, neighbor, and society. Whereas biographical approach is used in this study because Yakuza Moon is the memoirs novel from Shoko Tendo. Social psychological approach leads to open the relationship between Japanese society and Shoko Tendo`s psychological condition. Then, biographical approach can be used for digging the meaning of the story of Shoko. Tendo`s life. To meet the proper analysis and interpretation, this study uses Prejudice, Discrimination, and Stereotype theory.The result of this study reveals that the negative stigma which is addressed to Shoko Tendo creates bullying, intimidation, insult, and discrimination. This study also confirms that there are different treatments of Japanese`s society toward Shoko Tendo`s family which is first when Hiroyashu serves as Yakuza boss, and second when he retires. Whereas Shoko Tendo`s behavior is influenced by two factors, that are society and family.